Discovery of a novel CHD7 CHARGE syndrome variant by integrated omics analyses. Issue 2 (13th November 2020) - Granadillo, Jorge L.; Wegner, Daniel J.; Paul, Alexander J.; Willing, Marcia; Sisco, Kathleen; Tedder, Matthew L.; Sadikovic, Bekim; Wambach, Jennifer A.; Baldridge, Dustin; Cole, Francis Sessions
Abstract: Chromodomain helicase DNA‐binding protein 7 ( CHD7 ) pathogenic variants are identified in more than 90% of infants and children with CHARGE ( C oloboma of the iris, retina, and/or optic disk; congenital H eart defects, choanal A tresia, R etardation of growth and development, G enital hypoplasia, and characteristic outer and inner E ar anomalies and deafness) syndrome. Approximately, 10% of cases have no known genetic cause identified. We report a male child with clinical features of CHARGE syndrome and nondiagnostic genetic testing that included chromosomal microarray, CHD7 sequencing and deletion/duplication analysis, SEMA3E sequencing, and trio exome and whole‐genome sequencing (WGS). We used a comprehensive clinical assessment, genome‐wide methylation analysis (GMA), reanalysis of WGS data, and CHD7 RNA studies to discover a novel variant that causes CHD7 haploinsufficiency. The 7‐year‐old Hispanic male proband has typical phenotypic features of CHARGE syndrome. GMA revealed a CHD7 ‐associated epigenetic signature. Reanalysis of the WGS data with focused bioinformatic analysis of CHD7 detected a novel, de novo 15 base pair deletion in Intron 4 of CHD7 (c.2239‐20_2239‐6delGTCTTGGGTTTTTGT [NM_017780.3]). Using proband RNA, we confirmed that this novel deletion causes CHD7 haploinsufficiency by disrupting the canonical 3′ splice site and introducing a premature stop codon. Integrated genomic, epigenomic, and transcriptome analyses discovered a novel CHD7 variant that causes CHARGE syndrome.